Sustainable smart anti-corrosion coating materials derived from vegetable oil derivatives: a review. Issue 6 (27th January 2023) - Singh, Poonam; Rana, Anuj; Karak, Niranjan; Kumar, Indresh; Rana, Sravendra; Kumar, Pankaj
Abstract : The article covers coating materials using bio-chemical derived molecules (vegetable oils) and their properties including mechanical, self-healing and anti-corrosion properties. Abstract : Sustainable development is a critical concern in this fast-paced technological world. Therefore, it is essential to employ renewable resources to move towards sustainable development goals (SDGs). The polyols attained from renewable resources, including lignin, chitosan, vegetable oils, cellulose, etc. and the polymers derived from them have attracted the attention of the majority of researchers, both in academia and industry. The development of bio-based polymers from vegetable oils start emerging with different properties to generate a value-added system. This review will give an impression to readers about how coatings generated from vegetable oils can find a way towards better protective properties against corrosion either by using fillers or by using molecular structure modifications in the system, thus covering a range of vegetable oil-based self-healing polymers and their application in anti-corrosion coatings.